Visfatin-induced expression of inflammatory mediators in human endothelial cells through the NF-κB pathway - Lee, W-J; Wu, C-S; Lin, H; Lee, I-T; Wu, C-M; Tseng, J-J; Chou, M-M; Sheu, W H-H (International Journal of Obesity, 2009)
Background: Visfatin is an adipokine that is highly expressed in visceral fat. Plasma levels of visfatin have been reported to be higher in subjects with obesity and/or type 2 diabetes mellitus. However, the role of visfatin in endothelial dysfunction has been largely unexplored. Objectives: We investigated the possible pathogenic role of visfatin in endothelial dysfunction, particularly focusing on its effect on inflammatory mediators. Design: Primary human umbilical vein endothelial cells (HUVECs) pretreated with visfatin (1, 10 and 50 ng ml −1 ) were used to study the relationship between visfatin and endothelium dysfunction. Expressions of adhesion molecules (ICAM-1, VCAM-1 and E-selectin) and cytokines (interleukin (IL)-6 and IL-8) affected by visfatin were investigated by enzyme-linked immunosorbent assay, flow cytometry and real-time PCR. Activity of nuclear factor (NF)-κB was examined by electrophoretic mobility shift assay. Results: At a visfatin concentration of 50 ng ml −1 , significant increases in IL-6, IL-8, ICAM-1, VCAM-1 and E-selectin gene expression along with increased IL-6, IL-8 and sE-selectin protein levels in the conditioned medium were detected. Flow cytometry showed that the addition of visfatin significantly increased ICAM-1 expression and VCAM-1 expression (10 and 50 ng ml −1 , respectively). Electrophoretic mobility shift assay confirmed that visfatin increased the DNA-binding activity of NF-κB. In addition, pretreatment with visfatin (10 and 50 ng ml −1 ) increased human monocyte cell line THP-1 adhesion to HUVECs. Conclusions: Our findings suggest that visfatin causes endothelial dysfunction by increasing inflammatory and adhesion molecule expression at least partly through the upregulation of NF-κB activity.